THE ROLE OF THE SOCIAL YOUTH DEVELOPMENT HOME 1 TEBET JAKARTA IN RELIEVING TROUBLED ADOLESCENTS - Anam, Ahmad Misbahul; Emi Sari (Jurnal Bina Ummat: Membina dan Membentengi Ummat, 2024)
Research objectives: To find out and describe the role of the Taruma Jaya 1 Tebet Jakarta Youth Development Social Home in increasing the independence of abandoned and school dropouts. Research method: Qualitative. Research Results: The results of the study show that PSBB Taruma Jaya 1 has a role as a social welfare institution based on the Regulation of the Minister of Social Affairs Number 184 of 2011 article 5. First, as a prevention of social problems by providing nutritious food, clean housing, and free package schools to college. Second, as a social service provider by providing mental and spiritual guidance, skills guidance and physical guidance. Third, as an organizer of family welfare consultation, but in this 3rd role has not been implemented. Of the 3 roles that contribute a lot to improving the independence of fostered adolescents, the role as a social service provider. Conclusion: The role of PSBR Taruma Jaya 1 as a social welfare institution in increasing the independence of abandoned and out-of-school adolescents has been effectively implemented through the services, guidance, and rehabilitation that have been provided. This can be seen before entering the orphanage, the abandoned teenagers and school dropouts do not have skills, but after being fostered at PSBR Taruna Jaya 1 they already have provisions to be independent so that they can work in various companies